PERBANDINGAN KADAR KOLESTEROL HIGH DENSITY LIPOPROTEIN DARAH PADA PRIA PEROKOK DAN BUKAN PEROKOK - Gopdianto, Defitson Adolfo (Universitas Sam Ratulangi, 2013)
AbstractBackground: Decrease or increase in blood HDL cholesterol levels affect smokers and nonsmokers. Cigarettes have chemicals that can lead to several health problems such as nicotine. Nicotine resulted in the production of very low density lipoprotein(VLDL) in order to reduce redundant high density lipoprotein cholesterol levels.Method: This type of researchis anobservationalstudyusing across sectional design. Thisstudy populationisstudents ofthe Faculty ofMedicine, University ofSamRatulangi7th semesterof the school year2012/2013with apopulation of150people. Sampling technique inthis research is byusingpurposivesamplingtechniques, smokersand nonsmokersobtainedusing a questionnaire.Result: Determinedthatthere is astatisticallysignificant differencebetweenHDLcholesterol levelsin theblood ofmalesmokersand nonsmokersp=0.49.Cinclusion: There isstatistically significantdifferences inHDLcholesterol levelsin theblood ofmalesmokersand nonsmokers.Keywords: HDLcholesterol levels, smokers, and nonsmokersAbstrakLatar belakang: Penurunan atau peningkatan kadar kolesterol HDL darah berpengaruh pada perokok dan bukan perokok. Rokok memiliki bahan-bahan kimiawi yang dapat mengakibatkan beberapa gangguan kesehatan diantaranya adalah nikotin. Nicotineresulted inthe production ofvery low densitylipoprotein(VLDL) in order toreduceexcessivelevels ofhigh densitylipoproteincholesterol.Metode: Jenis penelitian merupakan penelitian observasional dengan menggunakan rancangan cross sectional.Populasi penelitian ini yaitu mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi semester 7 tahun ajaran 2012/2013 dengan besar populasi berjumlah 150 orang. Teknik pengambilan sampel pada penelitian ini yaitu dengan menggunakan teknik purposive sampling, perokok dan bukan perokok didapatkan dengan menggunakan kuesioner.Hasil:Secara statistik ditetapkan bahwa terdapat perbedaan yang bermakna antara kadar kolesterol HDL darah pada pria perokok dan bukan perokok p=0,49.Kesimpulan: Secara statistik ada perbedaan kadar kolesterol HDL darah pada pria perokok dan bukan perokok.Kata kunci: Kadar kolesterol HDL, perokok, dan bukan perokok.